2021
DOI: 10.1016/j.amsu.2021.102649
|View full text |Cite
|
Sign up to set email alerts
|

Fatal poisoning of pregnant women by peganum harmala L.: A case reports

Abstract: Introduction Peganum harmala L. is a cosmopolitan plant within the Mediterranean region. It's normally employed in ancient drugs in Morocco as sedative and abortifacient however exposes users to the danger of dose and poisoning. The medical specialty active compounds of this plant embody variety of carboline and quinazoline alkaloids accountable of its pharmacological and medical effects. Case report We tend to report the case of a 20-year-old woman, intoxicated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Neurological, gastrointestinal, and cardiovascular symptoms accounted for 34.4%, 31.9%, and 15.8% of the cases of poisoning, respectively. Following the consumption of P. harmala seeds, patients apply to the clinic with complaints such as visual and auditory hallucinations, locomotor ataxia, nausea, vomiting, confusion, and agitation (88)(89)(90)(91)(92)(93)(94)(95)(96). Some cases of poisoning by P. harmala are listed in Table 3.…”
Section: Human Toxicitymentioning
confidence: 99%
“…Neurological, gastrointestinal, and cardiovascular symptoms accounted for 34.4%, 31.9%, and 15.8% of the cases of poisoning, respectively. Following the consumption of P. harmala seeds, patients apply to the clinic with complaints such as visual and auditory hallucinations, locomotor ataxia, nausea, vomiting, confusion, and agitation (88)(89)(90)(91)(92)(93)(94)(95)(96). Some cases of poisoning by P. harmala are listed in Table 3.…”
Section: Human Toxicitymentioning
confidence: 99%
“…The corresponding concentrations were much lower in rats treated with a low P. harmala dose (15 mg/kg), with harmaline and harmine being barely detectable in plasma. This suggests a non-linear dose-response, making it difficult to extrapolate these results to human ingestion of P. harmala; there is a case report of fatal toxicity due to P. harmala ingestion (Ghizlane, 2021), whereas a study from Morocco indicated a 6% fatality rate in a series of 200 cases of poisoning marked by neurological, gastrointestinal and cardiovascular signs (Achour, 2012). We cannot attribute these effects to β-carbolines per se.…”
Section: The Physiological Relevance Of Mao Inhibition; the Case Of A...mentioning
confidence: 99%